2017
DOI: 10.1016/j.bbamem.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and cooperativity between P-glycoprotein structural domains determined by thermal unfolding provides insights into its solution structure and function

Abstract: Structural changes in mouse P-glycoprotein (Pgp) induced by thermal unfolding were studied by differential scanning calorimetry (DSC), circular dichroism and fluorescence spectroscopy to gain insight into the solution conformation(s) of this ABC transporter that may not be apparent from current crystal structures. DSC of reconstituted Pgp showed two thermal unfolding transitions in the absence of MgATP, suggesting that each transition involved the cooperative unfolding of two or more interacting structural dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…The far-UV CD spectrum of detergent-solubilized Pgp exhibited minima at 208 and 222 nm, as previously reported, and is typical for an α-helical protein (Fig. 6C) 84,85 . The shape of the far-UV CD spectra of W(3Cyto) and WL-Pgp was indistinguishable from Wt samples, suggesting that secondary and, in all likelihood, tertiary structure was maintained in the Trp mutants.…”
Section: Biophysical Characterization Of Purified W(3cyto) and Wl-pgpsupporting
confidence: 85%
See 1 more Smart Citation
“…The far-UV CD spectrum of detergent-solubilized Pgp exhibited minima at 208 and 222 nm, as previously reported, and is typical for an α-helical protein (Fig. 6C) 84,85 . The shape of the far-UV CD spectra of W(3Cyto) and WL-Pgp was indistinguishable from Wt samples, suggesting that secondary and, in all likelihood, tertiary structure was maintained in the Trp mutants.…”
Section: Biophysical Characterization Of Purified W(3cyto) and Wl-pgpsupporting
confidence: 85%
“…A second transition followed immediately after a sharp increase in the PMT voltage profile (gray circles, right axis). The increase in voltage suggested sample aggregation 85 , and coincided with a visible precipitation in the sample cuvette after heating above 50 °C. A comparison of the thermal unfolding profiles showed that the first transition was shifted to slightly lower temperatures in the W(3Cyto) (36.8 ± 0.5 °C), and significantly lower in the WL-Pgp (33.5 ± 0.3 °C).…”
Section: Biophysical Characterization Of Purified W(3cyto) and Wl-pgpmentioning
confidence: 73%
“…A similar +5 °C shift in T m Trp due to H1402S was consistently observed in ΔRI/2PT/H1402S, ΔRI/2PT/M470V/H1402S, and 6SS/H1402S, suggesting that the shift in conformational population enhanced structural stability of the protein. Indeed, a similar stabilizing effect was observed in P-glycoprotein with equivalent mutations that promoted the occluded NBD dimer conformation with trapped MgATP [72,73]. A large body of literature reports on conformational stabilization due to specific mutations and combinations of mutations in G-protein coupled receptors (GPCRs).…”
Section: Discussionmentioning
confidence: 84%
“…In those cases, conformational stabilization was essential to obtain crystal structures in different states [74], [75], [76], [77]. Thermal unfolding studies with P-glycoprotein and other membrane proteins have shown that unfolding of α-helical transmembrane domains is unlikely to be detected by Trp fluorescence over the temperature range of the present study [55,73,78,79]. In CFTR, 11 of the 23 intrinsic Trp residues are situated in transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…Most models for P-gp dynamics include intimate contact between NBD1 and NBD2 upon formation of the OF state, whereas they are well separated and apparently more solvent exposed in the IF state. In fact the NBDs thermodynamically stabilize one another in the vanadate-trapped state (29), which implies substantial inter-NBD interaction, as suggested by the effect of vanadate trapping on EX2 kinetics for many peptides spanning the NBDs. Thus, the combined H/DX results indicate that, either the expected contact between the NBDs upon vanadate trapping of the OF state only modestly affects solvent access to most structural elements including those that are stabilized by NBD dimer formation, or the NBDs remain in a dynamic equilibrium between states that allow solvent access even when the ATPase activity is persistently inhibited and the NBDs form a dimer.…”
Section: Discussionmentioning
confidence: 99%